Answer:
Second option: 81y^4 - 16x^2, the difference of squares
Step-by-step explanation:
(9y^2-4x)(9y^2+4x) is a special product named difference of squares, then we can apply this formula:
(a-b)(a+b)=a^2-b^2, with a=9y^2 and b=4x, then:
(9y^2-4x)(9y^2+4x)=(9y^2)^2 - (4x)^2
(9y^2-4x)(9y^2+4x)=(9)^2 (y^2)^2 - (4)^2 (x)^2
(9y^2-4x)(9y^2+4x)=81y^(2*2) - 16x^2
(9y^2-4x)(9y^2+4x)=81y^4 - 16x^2
Answer:
x=20
Step-by-step explanation:
Answer:
The system is consistent; it has one solution ⇒ D
Step-by-step explanation:
A consistent system of equations has at least one solution
- The consistent independent system has exactly 1 solution
- The consistent dependent system has infinitely many solutions
An inconsistent system has no solution
In the system of equations ax + by = c and dx + ey = f, if
- a = d, b = e, and c = f, then the system is consistent dependent and has infinitely many solutions
- a = d, b = e, and c ≠ f, then the system is inconsistent and has no solution
- a ≠ d, and/or b ≠ e, and/or c ≠ f, then the system is consistent independent and has exactly one solution
In the given system of equations
∵ -2y + 2x = 3 ⇒ (1)
∵ -5y + 5x = 12 ⇒ (2)
→ By comparing equations (1) and (2)
∵ -2 ≠ -5
∵ 2 ≠ 5
∵ 3 ≠ 12
→ By using the 3rd rule above
∴ The system is consistent independent and has exactly one solution
∴ The system is consistent; it has one solution
Answer: $40
Step-by-step explanation:
To find the whole number you divide the part by the percentage
so here it was 32/0.8
hope it helps